2012
DOI: 10.1007/s10695-012-9713-2
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine (plasma cortisol and glucose) and behavioral (locomotor and self-feeding activity) circadian rhythms in Senegalese sole (Solea senegalensis Kaup 1858) exposed to light/dark cycles or constant light

Abstract: The existence of daily rhythms under light/dark (LD) cycles in plasma cortisol, blood glucose and locomotor and self-feeding activities, as well as their persistence (circadian nature) under constant light (LL), was investigated in Senegalese sole (Solea senegalensis). For the cortisol and glucose rhythms study, 48 soles were equally distributed in 8 tanks and exposed to a 12:12 LD cycle and natural water temperature (experiment 1). After an acclimation period, blood was sampled every 3 h until a 24-h cycle wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 38 publications
7
42
0
Order By: Relevance
“…Such night increase in plasma cortisol was already described in salmonids . However, cortisol peaks happen during photophase at 15:00 in Senegalese sole and at light onset in goldfish and Eurasian perch . A previous experiment in pike perch also showed a cortisol peak at 10:00 during photophase while humoral immune activity peaks also occurred during the night as in the present experiment.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Such night increase in plasma cortisol was already described in salmonids . However, cortisol peaks happen during photophase at 15:00 in Senegalese sole and at light onset in goldfish and Eurasian perch . A previous experiment in pike perch also showed a cortisol peak at 10:00 during photophase while humoral immune activity peaks also occurred during the night as in the present experiment.…”
Section: Discussionsupporting
confidence: 87%
“…Cortisol, considered as a major stress marker in fish, plays a crucial role in several biological functions including stress response, growth, immune functions, and energy metabolism . In the present experiment, the increase in plasma cortisol at day 1 under a 100‐lx light confirmed that the exposure to high light intensities is stressful for pike perch.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Whether this significantly influenced our results is unclear and demands further research. As diurnal activity and endocrine (cortisol) rhythms in Senegal sole persisted under constant light conditions [24], we do not expect that results of our preference test were influenced by conducting them under constant light.…”
Section: Discussionmentioning
confidence: 85%
“…Senegal sole ( Solea senegalensis ) display a clear daily activity rhythm, with the highest activity during night hours [24]. Daily activity rhythms have not been experimentally assessed in Dover sole but these could be similar to Senegal sole as for the nocturnal nature of both species [25], [26].…”
Section: Discussionmentioning
confidence: 99%